COVID-19 transmission within a family cluster by presymptomatic carriers in China - Chen, Xiaomin; Chen, Xueqin; Li, Guoxiang; Wang, Liping; Ma, Ada Hoi Yan; Yang, Naibin; Qian, Guoqing (NLM (Medline), 2020)
We report a COVID-19 family cluster caused by a presymptomatic case. There were 9 family members, including 8 laboratory-confirmed with COVID-19, and a 6-year-old child had no evidence of infection. Amongst the 8 patients, one adult and one 13-month-old infant were asymptomatic, one adult was diagnosed as having severe pneumonia.